Beta-type means. Issue 5 (4th May 2018) - Himmel, Martin; Matkowski, Janusz
Abstract: Based on the relationship between the Beta and the Euler Gamma function, beta-type functions of several variables, generated by a single variable function, are introduced. Applying the method of iterative functional equations, all means of beta-type are determined and some of their properties are discussed.